2014
DOI: 10.5507/bp.2012.069
|View full text |Cite
|
Sign up to set email alerts
|

Per3 VNTR polymorphism and chronic heart failure

Abstract: Aims. The aim of this study was to investigate the relationship between gene Period3 (Per3) variable number tandem repeat (VNTR) polymorphism and chronic heart failure (CHF). Methods. The study subjects (372 patients of Caucasian origin with CHF and 332 healthy controls) were genotyped for Per3 VNTR polymorphism using an allele-specific PCR. Results. No significant differences in genotype or Per3 VNTR allele frequencies were found between CHF cases and controls (P g =0.30, P a =0.52). No significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…No significant difference was observed in allele periodicities of PER3 VNTR between the obese and the nonobese individuals (Bienertova-Vasku et al, 2014). In addition, there was no significant difference between chronic heart failure patients and controls regarding PER3 VNTR allele and genotype frequencies (Lipkova et al, 2014a). Geng et al (2015) found a moderate increase in risk of cancer among individuals with the PER3 VNTR 5 allele compared to individuals with the 4 allele in a meta-analysis.…”
Section: Discussionmentioning
confidence: 84%
“…No significant difference was observed in allele periodicities of PER3 VNTR between the obese and the nonobese individuals (Bienertova-Vasku et al, 2014). In addition, there was no significant difference between chronic heart failure patients and controls regarding PER3 VNTR allele and genotype frequencies (Lipkova et al, 2014a). Geng et al (2015) found a moderate increase in risk of cancer among individuals with the PER3 VNTR 5 allele compared to individuals with the 4 allele in a meta-analysis.…”
Section: Discussionmentioning
confidence: 84%
“…33 Furthermore, the PER3 clock gene is part of the circadian clock transcription/translation feedback loop and encodes a protein involved in sleep regulation. 17 PER3 has been studied concerning heart tissue and heart diseases, 21,[34][35][36] and SNPs of the PER3 gene have been confirmed to play an important role in the endocrine system and psychological disease progression. For example, effects on depression and anxiety symptoms 37 and melaton in treatment, 38 analysis of Graves' disease susceptibility, 39 and even effects on tumors such as breast cancer 40 have been proven in previous studies.…”
Section: Discussionmentioning
confidence: 99%